Odpowiedzi

Najlepsza Odpowiedź!
2010-01-27T12:40:24+01:00
A) 6(x-4)-2= 6x-24-2=6x-26
b)2(x+1)-3(x-1)= 2x+2-3x+3=-1x+5
c)-3(y-2)+4(y+2)=-3x+6+4y+8=1y+14
d)5(x-y-1)-4(x+2)= 5x-5y-5-4x-8=1x-5y-13
2010-01-27T12:40:27+01:00
A) 6(x-4)-2= 6x-24-2= 6x-26
b) 2(x+1)-3(x-1)= 2x+2-3x-4= -x-2
c) -3(y-2)+4(y+2)= -3y+6+4y+8=y+14
d) 5(x-y-1)-4(x+2)= 5x-5y-5-4x-8= x-5y-13

Mam nadzieje, że pomogłam
Pozdrawiam!!
1 5 1
2010-01-27T12:41:40+01:00
A) 6(x-4)-2=6x-24-2=6x-26

b) 2(x+1)-3(x-1)=2x+2-3x+3=-x+5

c) -3(y-2)+4(y+2)=-3y+6+4y+8=y=+14

d) 5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13